Molecular characterization of begomovirus–betasatellite–alphasatellite complex associated with okra enation leaf curl disease in Northern Sri Lanka - Jeyaseelan, E.C.; Sharmya, M.; Michael Warren, S. (Springer, 2020)
Okra enation leaf curl is a newly emerging disease in commercial okra cultivation felds in Northern Sri Lanka. The present study aimed to identify and characterize the causative begomovirus and associated satellites. Okra plants showing the enation leaf curl disease symptoms were collected from Vavuniya and Jafna districts of Northern Province. The PCR diagnostic and genome sequencing revealed that the symptomatic okra plants are associated with begomovirus, betasatellite, and alphasatellite complex. The begomovirus isolates shared 98.2–99.7% nucleotide identity with Okra enation leaf curl virus. The betasatellites showed 96–98.8% nucleotide identity with Bhendi yellow vein mosaic betasatellite which is usually associated with Bhendi yellow vein mosaic disease. Two distinct alphasatellite species, Okra leaf curl alphasatellite and Bhendi yellow vein mosaic alphasatellite, were identifed in leaf samples with enation leaf curl disease. The disease was transmitted by whitefies from diseased plants to healthy plants. Hybrid varieties were more susceptible to the disease compared to cultivated varieties.
Keywords: Okra enation leaf curl; Begomovirus; Betasatellite; Alphasatellite